Eksistensi Diplomat Indonesia di Forum Majelis Umum PBB 2016-2021 dalam Menghadapi Tuntutan Papua Merdeka Oleh Delegasi Vanuatu - Febriyanti Febriyanti; Franky P Roring, M. Si (Jurnal Communitarian (Prodi Ilmu Politik), 2022)
ABSTRACTThis study describes the existence of Indonesian diplomats in answering Vanuatu's questions regarding human rights violations in Papua in the UN General Assembly forum. The ethnic closeness that Vanuatu has with Papua, namely the Melanesian race, is one of the reasons Vanuatu is increasingly massive in supporting the independence of West Papua. This study uses a qualitative descriptive analysis research methodology accompanied by interview data collection techniques as primary data and literature study as secondary data. The conclusion of this study is that the success of Indonesia's diplomacy in the UN General Assembly forum cannot be separated from the ability of Indonesian diplomats to answer and analyze problems that occur in the forum. The attitude and behavior of diplomats is something that is indispensable in the process of diplomacy at the UN General Assembly. Keywords: Existence of Diplomats, Diplomacy, and Neo-realists